Pace of alcohol drinking during in natural-environment drinking is associated with heightened alcohol-related reward and negative consequences in risky drinkers. - Atkinson, Emily A.; Fischer, Andrew M.; Cursio, John F.; King, Andrea C.; Fridberg, Daniel J. (Psychopharmacology, 2025)
Background: Sensitivity to alcohol's stimulating and rewarding properties is associated with increased risk for future heavy drinking and the development and maintenance of alcohol use disorder (AUD). Further, pace of alcohol consumption varies across individuals and affects level of intoxication and subjective alcohol responses. The present study used smartphone-based high-resolution ecological momentary assessment (HR-EMA) of a heavy drinking episode in young adult risky drinkers' natural environments to examine associations between pace of drinking and subjective responses to alcohol. Method: Young adult risky drinkers (N = 248; 42% female) completed a 3-hour HR-EMA of alcohol use and subjective responses to alcohol (stimulation, sedation, feeling, liking, and wanting more) during a drinking episode in their natural environment. Analyses examined associations between drinking pace trajectories and subjective responses to alcohol, accounting for drinking context (location/presence of others) and depression. Results: Trajectory analysis revealed three drinking pace subgroups based on total drinks consumed during the 3-hour monitoring period: fast risers (~ 4 standard drinks/hour), moderate risers (~ 2.6 standard drinks/hour), and slow risers (~ 1.4 standard drinks/hour). Overall, faster pace of drinking was associated with greater alcohol stimulation and reward (liking and wanting more) and more alcohol-related negative consequences during and after the episode. Conclusions: Results further underscore the heterogeneous nature of young adult risky drinkers and suggest the possibility that these individuals may drink rapidly to experience the stimulating and rewarding effects of alcohol sooner. Resulting increases in the positive effects of alcohol may reinforce future rapid drinking behavior.